The Role of Chatbots in Supporting Distance Learning - Safitri, Sefia Diana (Universitas Nurul Jadid Probolinggo, Indonesia, 2024)
This research aims to explain the role of chatbots in supporting distance learning activities and their impact on the effectiveness of students' learning processes. The study employs a qualitative approach to explore how chatbot features, such as personalized responses, effective real-time feedback, and reflective interaction, influence students' learning experiences. Data was collected through in-depth interviews with teachers, educational technology experts, and students, as well as analysis of interactions with the chatbot. The findings indicate that chatbots with good personalized responses and effective real-time feedback significantly enhance student engagement and the quality of interactions in distance learning. This research contributes to the literature by providing new perspectives on the application of chatbot technology in education, as well as insights into how these features can improve student learning experiences and outcomes.